2023
DOI: 10.1002/1878-0261.13571
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and signaling crosstalk in glioblastoma progression and therapy resistance

Laura Zarzuela,
Raúl V. Durán,
Mercedes Tomé

Abstract: Glioblastoma is the most common form of primary malignant brain tumor in adults and one of the most lethal human cancers, with high recurrence and therapy resistance. Glioblastoma cells display extensive genetic and cellular heterogeneity, which precludes a unique and common therapeutic approach. The standard of care in glioblastoma patients includes surgery followed by radiotherapy plus concomitant temozolomide. As in many other cancers, cell signaling is deeply affected due to mutations or alterations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Metabolomics, the study of small molecule metabolites in biological systems, has emerged as a powerful tool for understanding the metabolic alterations in glioblastoma cells and identifying potential therapeutic targets. Studies in metabolomics, including those focusing on glioblastoma, have identified several altered or dysregulated metabolic pathways in comparison to healthy cells [3][4][5][6][7][8]. Examples of these alterations include changes in glucose and amino acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics, the study of small molecule metabolites in biological systems, has emerged as a powerful tool for understanding the metabolic alterations in glioblastoma cells and identifying potential therapeutic targets. Studies in metabolomics, including those focusing on glioblastoma, have identified several altered or dysregulated metabolic pathways in comparison to healthy cells [3][4][5][6][7][8]. Examples of these alterations include changes in glucose and amino acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma cells have been shown to rely on glucose and several amino acids to support their high energy demands [9][10][11][12][13][14], as well as to utilize their carbon skeletons for anabolic processes such as lipid [15,16] and nucleotide synthesis [17]. Despite the genetic and cellular heterogeneity observed in glioblastoma cells within tumor [4], as well as heterogeneity in their metabolism [18][19][20], targeting metabolic pathways has emerged as a promising therapeutic strategy. Therefore, further studies focusing on and revealing the metabolic aspects of cancer cells could provide the valuable knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics, the study of small molecule metabolites in biological systems, has emerged as a powerful tool for understanding the metabolic alterations in glioblastoma cells and identifying potential therapeutic targets. Studies in metabolomics, including those focusing on glioblastoma, have identified several altered or dysregulated metabolic pathways in comparison to healthy cells [ 3 , 4 , 5 , 6 , 7 , 8 ]. Examples of these alterations include changes in glucose and amino acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma cells have been shown to rely on glucose and several amino acids to support their high energy demands [ 9 , 10 , 11 , 12 , 13 , 14 ], as well as to utilize their carbon skeletons for anabolic processes such as lipid [ 15 , 16 ] and nucleotide synthesis [ 17 ]. Despite the genetic and cellular heterogeneity observed in glioblastoma cells within tumors [ 4 ], as well as heterogeneity in their metabolism [ 18 , 19 , 20 ], targeting metabolic pathways has emerged as a promising therapeutic strategy. Therefore, further studies focusing on and revealing the metabolic aspects of cancer cells could provide valuable knowledge.…”
Section: Introductionmentioning
confidence: 99%